Large-scale LES analysis for aerodynamics of a group of racing bicycles by lattice Boltzmann method - Yuta HASEGAWA; Takayuki AOKI; Hiromichi KOBAYASHI; Keita SHIRASAKI (Nihon Kikai Gakkai ronbunshu, 2019)
We implement and perform large-scale LES analysis for running groups of cyclists. The mesh-refined lattice Boltzmann method (LBM) and coherent-structure Smagorinsky model (CSM) are adopted for the simulations to achieve a high performance computing on the recent GPU supercomputer. In the simulation with 16 cyclists, the mesh spacing around cyclists is 4 mm, and the total number of the mesh is up to 8.1×108 and the number of GPUs utilized is up to 64. Each calculation took 4 or 5 days for the 8～11 seconds of physical duration. The flow around 16 cyclists in various arrangement is calculated, and the results show that the in-line arrangement is more effective than the rhomboid arrangement in the viewpoint of the total aerodynamic drag of the group; however, a specific person in rhomboid arrangement can obtain larger drag reduction and save the endurance. Results on two groups also suggest that the frontal group in rhomboid arrangement will be exploited as the wind protection of the backward groups.